ORANG-ORANG YANG BERDAMAI DENGAN KEMISKINAN - Effendi, Chairil (Universitas Tanjungpura, 2023)
Orang-orang Biasa (Ordinary People ¸ 2019) is the second latest novel authored by Andrea Hirata before Guru Aini (2020). Similar to his other literary works, this novel employs the Malay society